"Lichenoid Granulomatous Pattern" in a Case of Lupus Vulgaris - Chirag Desai; Ismail Shaikh (MDPI AG, 2022)
Lupus vulgaris is a one of the most common skin infections in the Indian subcontinent. Even today, it often creates a diagnostic dilemma for both clinicians and histopathologists. We describe a case of lupus vulgaris that showed lichenoid granulomatous inflammation in the dermis. This pattern is not uncommon, but is rarely described in the literature as newer modalities currently take precedence in diagnosis. Our aim is to make clinicians and dermatopathologists aware of this pattern of inflammation seen in this common infection.